Acute response of biochemical bone turnover markers and the associated ground reaction forces to high-impact exercise in postmenopausal women - Prawiradilaga, Rizky; Madsen, Anders; Jørgensen, Niklas; Helge, Eva (Biology of Sport, 2020)
The aim of the study was to examine the acute response of biochemical bone turnover markers (BTM) to high-impact jumping exercise, and to quantify the ground reaction forces (GRF) achieved during each jumping exercise, in postmenopausal women. In a randomized controlled cross-over study over three days, 29 postmenopausal women (age (mean±SD): 60.0±5.6 years) were randomly assigned to 6 x 10 repetitions of three different jumps: countermovement jump (CMJ), drop jump (DJ), diagonal drop jump (DDJ). A fourth day without jumping served as a control (CON). Blood samples were collected before (PRE), after (POST), and 2 hours after (2Hr) exercise. Bone turnover was evaluated by bone formation markers (procollagen type-1 aminoterminal propeptide (P1NP) and osteocalcin (OC)) and the bone resorption marker C-terminal telopeptide of type-1 collagen (CTX). Peak anteroposterior (Fx), mediolateral (Fy), and vertical (Fz) GRF were measured using a force platform. From PRE to POST, P1NP increased (p<0.01) by 7.7±1.8%, 9.4±1.3%, and 10.6±1.6% for CMJ, DJ, and DDJ, which were higher (p<0.01) than CON. OC increased (p<0.05) by 5.5±1.8% for DJ, which was higher (p<0.05) than CON. CTX was not significantly changed at POST. There were no significant differences in BTM Δ-values between the jumps at any time point. For the CMJ, the combined three-axis peak GRF was positively associated with the PRE to POST Δ-change in P1NP (r=0.71, p<0.05). The acute, jumping-induced increase in P1NP and OC without any rise in CTX may indicate increased bone formation. Moreover, the study shows a dose-response relationship between GRF and the acute P1NP response after countermovement jumps.